Reverse spontaneous laser line sweeping in ytterbium fiber laser. (17th January 2017) - Navratil, P; Peterka, P; Honzatko, P; Kubecek, V
Abstract: Self-induced laser line sweeping of various regimes of sweep direction is reported for an experimental ytterbium fiber laser. The regimes involve sweeping from shorter to longer wavelengths ( 1076   n m → 1083 nm)—so-called normal self-sweeping; from longer to shorter wavelengths ( 1079   n m → 1073 nm)—so-called reverse self-sweeping; and a mixed regime in which a precarious balance of the normal and reverse sweeping exists and the sweep direction can change between consecutive sweeps. The regimes of sweeping were selected by changing the pump wavelength only. A detailed explanation of this sweep direction dynamics is presented based on a semi-empirical model. This model also provides a way to predict the sweep direction of fiber lasers based on other rare-earth-doped laser media.